INFLAMMATORY ACTIVITY AND RENAL PATHOLOGY IN LUPUS NEPHRITIS - Hamraeva Nasiba Abdurasulovna; Islamova Kamola Akramovna; Abdushukurova Komila Rustamovna; Xamrayev Botir Egamkulovich (Journals Park Publishing, 2023)
To solve the problems in the surveyed 45 patients: examination, laboratory complex, immune and instrumental methods. All 45 patients with SLE kidney disease manifested itself in the form of lupus nephritis. Syndrome hypertension vstre-chalsya in 35.5% of cases, the syndrome of chronic renal failure in 37.7% of cases. Urinary syndrome characterized by moderate proteinuria (75.5%), hematuria (73.3%) and leukocyturia (73.3%). Positive correlation of tumor necrosis factor α, C-reactive protein level of creatinine, urea, ESR and SLE activity, which confirms the participation of the factors described in the immune process lupus inflammation.
Keywords: systemic lupus erythematosus, kidney disease, tumor necrosis factor α, C-reactive protein.